Membentuk Kesadaran Literasi Digital Dengan Filtrasi Informasi Media Pada Mahasiswa Hukum Universitas Syiah Kuala - Arfan, Rahmat; Rizky , Fitrian; Hamdani, Hamdani; Ariansyah, Ricky; Ramadana, Sri Winarsih; Rahmaniar, Rahmaniar; Maulina, Rina (Apik Cahaya Ilmu, 2025)
The digital literacy training is designed to equip students and the general public with the ability to filter information effectively and efficiently. By applying media filtration concepts such as source verification, cross-checking facts, utilizing anti-hoax tools, and employing critical reasoning, participants are expected to increase control over the information they consume, thereby mitigating the negative impacts of fake news. The event was set in the Unsyiah mootcourt hall and attended by the general public and the Unsyiah community, with activities running throughout the day. This activity received a warm welcome from participants, who actively participated in discussions and asked questions about the development of circulating information and the filtering of such information